Coinfection of High-Risk Human Papillomavirus and Lower Genital Tract Pathogens in the Development of High-Grade Cervical Lesions. (30th August 2020) - Zhong, Hui; Tong, Yao; Lin, Haifeng; Mao, Xiaodan; Dong, Binhua; Wu, Zhihui; Chen, Huiyu; Sun, Pengming
Abstract : Purpose . This study investigated the infection status and relationship between other common lower genital tract infectious pathogens and high-risk human papillomavirus (HR-HPV) in the high-grade cervical lesions. Methods . Overall, 882 patients were enrolled in this retrospective study, of which 339 patients (≥HSIL group) were confirmed with high-grade squamous intraepithelial lesions (HSIL) or cervical squamous cell carcinoma (SCC), while 543 patients (≤LSIL group) were diagnosed with low-grade squamous intraepithelial lesions (LSIL) or normal cervical pathology diagnosis. Cervical swab specimens were tested for HPV, pathogenic bacteria (PB), U. urealyticum (UU), M. hominis (MH), and C. trachomatis (CT) in both groups. Results . The infection rates of HR-HPV, PB, UU (at high density), and CT were higher in the ≥HSIL group than in the ≤LSIL group (P < 0.001 ); however, higher infection rates with MH were not observed (P > 0.05 ). PB, UU, and CT were associated with HR-HPV infection (P < 0.001 ). The PB and UU infection rates in the ≥HSIL group were significantly different from those in the ≤LSIL group, regardless of whether there was an HR-HPV infection at the same time (P < 0.05 ). However, this was not the case for the CT (P > 0.05 ). Furthermore, 259 pathogenic bacterial strains were detected in 882 cases. The difference in the distribution of pathogenic bacterial flora in the different grades of cervical lesions had no statistical significance, which was prioritized over Escherichia coli (P > 0.05 ). Conclusion . PB, UU, and CT infection is associated with susceptibility to HR-HPV, HR-HPV coinfection with these pathogens might increase the risk of high-grade cervical lesions, and PB and UU might be independent risk factors for cervical lesions.